2016
DOI: 10.1021/acs.energyfuels.6b00757
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Sulfur Heteroatom on Asphaltene Aggregation

Abstract: We present molecular dynamics simulations (MDS) for interpreting the molecular aggregation of four different asphaltene molecular models. These simulations are based on recent small-angle X-ray scattering (SAXS) and small-angle neutron scattering (SANS) experiments from Eyssautier and co-workers [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 35 publications
3
55
0
Order By: Relevance
“…In previous work based on molecular dynamics simulations, we have shown that (i) polar acidic lateral chains play a major role favoring this aggregation pattern 18,19 and (ii) porphyrins are inherently present in these molecular aggregates forming multiple H-bonds with asphaltenes and water. 20 More particularly, we have also shown that vanadium porphyrins play an important role on asphaltene aggregation and water/oil interfacial activity.…”
Section: Introductionmentioning
confidence: 88%
“…In previous work based on molecular dynamics simulations, we have shown that (i) polar acidic lateral chains play a major role favoring this aggregation pattern 18,19 and (ii) porphyrins are inherently present in these molecular aggregates forming multiple H-bonds with asphaltenes and water. 20 More particularly, we have also shown that vanadium porphyrins play an important role on asphaltene aggregation and water/oil interfacial activity.…”
Section: Introductionmentioning
confidence: 88%
“…Recently, a breakthrough was made by using atomic force microscopy and molecular imaging of these aggregates [117]. Recent molecular dynamics simulations on realistic ''inland continental" structure of asphaltenes show the role of hetero-atoms such as nitrogen and sulphur in the aggregation processes [118,119]. For an asphaltene concentration of c asph = 9 wt%, the distance between macroaggregates is approximately hdi = 7.3 nm, which gives a very small pore space about 2 nm, ensuring a quasi 1D translational diffusion for most of hydrocarbon-distribution within the low porosity of the transient porous network of quasi immobile asphaltene macro-aggregates (Fig.…”
Section: Relations Between Nmr Relaxation Times Diffusion Coefficienmentioning
confidence: 99%
“…• Studied the role of heteroatom substitution on the conjugated core and the effect of mixing different asphaltenes together, showing that such substitutions do not modify the shape of the nanoaggregate but change considerably the energy of interaction between asphaltene molecules (Santos Silva et al 2016); • Presented solid arguments allowing one to identify the role of some heteroatoms when they are found in the lateral chains: Oxygen easily induces the formation of hydrogen bonds that change drastically how nanoaggregates interact; sulfur can also induce S-O interactions (Sodero et al 2016), and so on; • Demonstrated that porphyrins, when they have no lateral chain grafted to their core, have interactions with asphaltenes that are similar to asphaltene-asphaltene interactions as well, besides the fact that vanadyl porphyrins can also form hydrogen bonds with the asphaltenes, even those which have no polar lateral chain (Santos Silva et al 2017b); and • Shown that asphaltene nanoaggregation depends on the shape and size of the conjugated core and on the possibility of forming hydrogen bonds with their environment (Santos Silva et al 2017a).…”
Section: Introductionmentioning
confidence: 99%